Analiza nujnih pregledov v ortopedski ambulanti v Ljubljani - Gelebešev, Lasko (Informatica Medica Slovenica, 2011)
Medical records of all patients referred as urgent cases to the Orthopaedic Outpatient Clinic in Ljubljana in July 2009 were reviewed. ICD diagnoses, diagnostic imaging procedures, modalities of prescribed physical therapy (PT), referral to physical and rehabilitation medicine (PRM) specialists, and duration of problems before the visit were examined. At least one PT was prescribed in 43% of the cases. The patient was referred to a PRM specialist in only 3% of the cases. The problems had lasted from one day to several years (median 1 month). Because many non-urgent patients suffering from chronic musculoskeletal diseases are referred to orthopaedic surgeons, co-operation with PRM specialist should be improved. Data quality, especially coding the diagnoses according to the ICD, should also be ameliorated.
Keywords: ambulanta; analiza; medicinska dokumentacija; ortopedija; Slovenija